MENINGKATKAN HASIL BELAJAR ISWA DALAM PEMBELAJARAN SENI TARI DENGAN METODE COOPERATIVE LEARNING PADA KELAS XI IPS 2 DI SMA NEGERI 1 PULAU PUNJUNG - Hidayatul Meidiani; Yuliasma Yuliasma; Afifah Asriati (SENDRATASIK UNP, 2017)
AbstractThis article the aim  to describe students’ learning outcome in learning dance at grade XI IPS 2 of SMA 1 Pulau Punjung. It was assumed that using conventional teaching method led to low outcome of students’ result. The design of this study was classroom action research by using descriptive method to describe the action and the reaction which occurred in the field. The data were attained by using observation sheet and test for students who learnt by using cooperative learning method. The test included students’ ability in using body, sense, and rhythm with indicators of motion accuracy, movement memorization, expression in dance and precision of musical accompaniment and movement. The data were analyzed by using percentage formula, discussion and conclusion. The result showed that the implementation of cooperative learning method was able to improve students’ learning outcome. In cycle I the average score was 61.29% and in cycle II the average score was 82.59%. Therefore, cooperative learning method can be used to improve students’ learning outcome in learning dance at SMAN 1 Pulau Punjung.Keywords: Learning outcomes, Method, Dance